Infrared Fe II emission in narrow-line Seyfert 1 galaxies - Rodriguez-Ardila, Alberto (2002)
We obtained 0.8-2.4 μm spectra at a resolution of 320 km s-ˡ of four narrow-line Seyfert 1 galaxies in order to study the near-infrared properties of these objects. We focus on the analysis of the Fe II emission in that region and the kinematics of the low-ionization broad lines. We show that the 1 μm Fe II lines (λ9997, λ10501, λ10863, and λ11126) are the strongest Fe II lines in the observed interval. For the first time, primary cascade lines of Fe II arising from the decay of upper levels pumped by Lyα fluorescence are resolved and identified in active galactic nuclei. Excitation mechanisms leading to the emission of the 1 μm Fe II features are discussed. A combination of Lyα fluorescence and collisional excitation is found to be the main contributor. The flux ratio between near-IR Fe II lines varies from object to object, in contrast to what is observed in the optical region. A good correlation between the 1 μm and optical Fe II emission is found. This suggests that the upper z 4 F 0 and z 4 D 0 levels from which the bulk of the optical Fe II lines descend are mainly populated by the transitions leading to the 1 μm lines. The width and profile shape of Fe II λ11127, Ca II λ8642, and O I λ8446 are very similar but significantly narrower than Paβ, giving strong observational support to the hypothesis that the regions where Fe II, Ca II, and O I are produced are cospatial, interrelated kinematically, and most probably located in the outermost portion of the broad-line region.